PHONOLOGICAL PHENOMENA IN THE MUSNAD OF IMAM HASSAN AL-ASKARI, PEACE BE UPON HIM - Hamza, Ali Awad Mizer (Journal of Higher Education and Academic Advancement, 2024)
General Background: Phonetic analysis plays a crucial role in understanding the effectiveness of prose in communication, particularly in how it uses sound to enhance expression and achieve intended effects. This study focuses on the phonetic features in the Musnad of Imam Hassan Al-Askari (peace be upon him), examining how vocal phenomena contribute to the harmony and expressiveness of his texts. Specific Background: The Musnad is analyzed for its use of assimilation, substitution, and phonetic similarity, revealing how these features optimize pronunciation and influence. Assimilation is observed in the integration of homophones and closely related sounds, while substitution involves replacing phonetic elements to ease articulation. Phonetic similarity encompasses adjustments to maintain vocal harmony and fluidity. Knowledge Gap: Previous studies have not extensively analyzed the application of these phonetic phenomena in historical religious texts or their impact on the communicative effectiveness and aesthetic qualities of the text. Aims: This research aims to elucidate the role of phonetic phenomena in Imam Al-Askari's Musnad, highlighting how these elements facilitate communication and enhance the text’s persuasive power. Results: The analysis demonstrates that assimilation and substitution reduce muscular effort and achieve phonetic ease, while phonetic similarity ensures smooth and harmonious pronunciation. The Musnad reflects a sophisticated use of these phenomena to balance clarity and expressiveness, contributing to its effectiveness in conveying messages. Novelty: This study provides a novel perspective on the phonetic techniques used in historical Islamic texts, offering insights into their strategic application for enhancing linguistic performance. Implications: Understanding these phonetic strategies enriches the interpretation of classical texts and informs contemporary linguistic and literary analysis, emphasizing the enduring relevance of phonetic considerations in effective communication.